(untitled) (Journal of Partial Differential Equations, 2021)
This article presents some important results of conformable fractional partial derivatives. The conformable triple Laplace and Sumudu transform are coupled with the Adomian decomposition method where a new method is proposed to solve nonlinear partial differential equations in 3-space. Moreover, mathematical experiments are provided to verify the performance of the proposed method. A fundamental question that is treated in this work: is whether using the Laplace and Sumudu transforms yield the same results? This question is amply answered in the realm of the proposed applications.